The association between health behaviours and academic performance moderated by trait mindfulness amongst university students: an observational study - Heller, Sebastian; Reichel, Jennifer L.; Mülder, Lina M.; Schäfer, Markus; Schwab, Lisa; Werner, Antonia M.; Letzel, Stephan; Rigotti, Thomas; Dietz, Pavel (Frontiers in Public Health, 2024)
Objectives To target health communication at less health-conscious groups, evidence on health behaviours’ effects on non-health-related outcomes – such as academic performance – is necessary. Recent research has highlighted the associations of various health behaviours on academic performance of university students. However, there is a lack of research investigating the most predominant health behaviours simultaneously and their association with academic performance, as well as the factors that potentially influence the direction or strength of these associations. Therefore, this study investigated (I) which of the predominant health behaviours (physical activity, healthy diet, sleep, sedentary behaviour, alcohol consumption, smoking, drug use) are most associated with academic performance and (II) whether the personal resource of trait mindfulness moderates these associations. Methods An online survey was conducted amongst university students during the 2021 summer semester. Group differences in academic performance regarding health behaviours were analysed using ANOVA (N = 1,049). A first linear regression model (N = 571), considering all selected health behaviours simultaneously, assessed their association with academic performance. A second model (N = 540) assessed interaction effects of health behaviours and trait mindfulness. Separate regressions assessed each interaction’s association with academic performance. Results Sleep, fruit and vegetable consumption, and gender were significantly associated with academic performance. The second model showed no significant interaction effects. Conclusion Targeting sleep and fruit and vegetable consumption might be the most promising strategies for elevating students’ academic performance, thereby enabling health communication strategies to reach groups driven by performance improvements rather than health benefits.